Does living together or apart matter? A longitudinal analysis of relationship formation in later life in association with health, well-being, and life satisfaction. (May 2021) - Ševčíková, Anna; Juhová, Dana Seryjová; Blinka, Lukas; Gottfried, Jaroslav; Elavsky, Steriani; Ťápal, Adam
Despite a growing body of research on later-life relationship formation, little is known about the health predictors and outcomes of later-life Living-Apart-Together (LAT) relationships. A LAT living arrangement is understood to be a possible way for older adults with age-related limits to partner and balance the consequences of being single. Using both selection and resource models to capture the links between health and relationship status, we analyzed unpartnered people 50+ from the longitudinal Survey of Health, Ageing and Retirement in Europe. We examined who entered LAT or cohabiting relationships between Time 1 and 2, who remained unpartnered, and what effect the transition into one of these statuses had on the well-being of those who remained in that status at Time 3. The respondents in LAT relationships did not differ from their cohabiting counterparts in health indicators before the relationship formation, nor was there a difference in life satisfaction and well-being 2 years after partnering. Compared to unpartnered persons, LAT respondents reported better self-perceived health before relationship formation and slightly higher life satisfaction 2 years later. Health status does not influence the choice for a relationship form, but a LAT relationship may constitute a resourceful living arrangement in later life, which provides some support for both the selection and resource models.